IMPROVING THE CONTENT AND METHODOLOGY OF TEACHING QUANTUM PHYSICS IN ACADEMIC LYCEUMS (Scientific journal of the Fergana State University, 2023)
The article shows the emergence and development of science in the study of quantum physics. In order to improve the content and methods of teaching the section of quantum physics in academic lyceums in the field of exact sciences and in areas where physics is studied in depth, it is included in the curriculum developed for the section “Quantum physics” in academic lyceums, when conducting topics they will have in-depth knowledge on the study of the topics “Quantum physics” in academic lyceums, where physics is carried out in depth.